The Development of Preschool Children during the COVID-19 Pandemic - Maghfuroh, Lilis; Harmiardillah, Sylvi; Samantha, Harnina; Eko Martini, Diah; Ekawati, Heny (The Indonesian Journal of Health Science, 2023)
Children are the dream of every family, the preschool period is a period of increasing development so that it is expected to develop optimally according to their age. The purpose of this study was to analyze the factors that influence the development of preschool children during the COVID-19 pandemic, namely the factors of children's diet, child's nutritional status, child's gender, parents' education, parents' age, and parent's occupation. This research is a quantitative research that uses a correlation analytic design with a cross-sectional type of design. The sampling used was simple random sampling with a population of 53 and a sample of 47 preschool children aged 3-6 years at Tunas Melati Kindergarten, Cluring Village, Kalitengah District, Lamongan. Data analysis using SPSS for Windows 23 with Spearman, Mann Whitney, and Pearson correlation statistical tests. The results of the study showed that almost all of the parents were 20-35 years old, more than half of the parents had high school education, more than half of the parents were working status, more than half of the gender were girls, more than half of the children's diet was moderate, more than half of the children's status. normal child nutrition, and more than part of the child's development according to his age. The results of statistical tests show that there is a relationship between diet and nutritional status with the development of preschool children during the COVID- 19 pandemic, there is no relationship between parental age, parental education, parental occupation, and gender of children with the development of preschool children during the COVID-19 pandemic.